A Note on Lapsi Production in Bhaktapur District of Nepal - Rajbhandari Joshi, Rinita (Journal of Development and Administrative Studies, 2018)
Lapsi (Choerospondias axillaris: an indigenous fruit tree of Nepal) is grown in temperate climate. The study of socio-economy of Lapsi Fruits in Bhaktapur District of Nepal was conducted in 2016. Bhaktapur district is selected on the basis of coverage area of Lapsi production, processing small scale industries, marketing value and its use by consumers. Forty respondents are selected and interviewed for group discussion and collection of primary and secondary data from different institutions. The coverage of production area of Lapsi fruits is 198.0 hectare and total production is 105.0 metric ton with productivity of 0.9 metric ton per hectare. The harvested Lapsi fruits are sold to local and urban markets. Major processed products of Lapsi fruit are Candy sweet, Candy hot, Titaura, Mada, Pickle, Jam and Lapsi powder. The overall average cost of production of Lapsi fruits is NRs. 2250.0/ropani and gross return NRs.7150.0/ropani with net profit of NRs4900.0/ropani. Therefore, the benefit cost ratio is 3.1. The wholesale prices of the products Mada, Titaura, Candy sweet, Candy hot, Pickle, Jam and Powder are NRs,.105.0/Kg, NRs.158.0/Kg, NRs.175.0, NRs. 190.0/Kg, NRs290.0/Kg, NRs225.0/Kg and NRs275.0/Kg respectively. The study findings suggest that improved varieties of Lapsi fruits should be disseminated to local farmers to increase in production. Government policies should be clear to facilitate Lapsi fruits producers with loans of minimum interest. The quality products of Lapsi candies should be exported as it helps to earn foreign currency and promotes economic development of Nepal. The Journal of Development and Administrative Studies (JODAS) Vol. 24 (1-2), pp. 63-70